APPLICATION OF THE DESIGN THINKING METHOD FOR THE UI/UX DESIGN OF THE MASBON APPETIT CAFE APPLICATION TO IMPROVE USER INVOLVEMENT - Davit Hermawan Davit; Nurdiansyah Permana; Endra Abdul Hadi; Raden Deden Ahmad Hidayat; Enang Rusnandi (Journal of Multimedia Technology and Applied Software, 2025)
This research focuses on designing an intuitive and engaging user interface (UI) for the food ordering app at Cafe Masbon Appetit. In the rapidly evolving digital technology landscape, the challenge of interface design often arises when it fails to match actual user needs. This directly impacts low levels of user satisfaction and engagement, a crucial issue that needs to be addressed to ensure the app's adoption and sustainability. To address this issue, we adopted a Design Thinking approach. This methodology was chosen for its ability to foster innovative, human-centered solutions, to improve user convenience, ease of use, and overall interaction with the app. The research process began with the collection of comprehensive user needs data through in-depth interviews and questionnaires distributed to the target audience. The collected information was then analyzed to identify pain points and user preferences. Based on the data obtained, the design solution was realized in the form of an interactive prototype. This prototype was then tested for effectiveness through a series of user tests to validate its functionality and usability. The research results consistently showed that the app successfully provided significant convenience in the food ordering process, increased time efficiency, and delivered a significantly better user experience. This was reflected in the high usability scores, which reflected a substantial level of user satisfaction.